Penentuan waktu baku untuk memproduksi produk rak buku menggunakan metode jam henti di CV. AFW - Amalia, Akhsani Nur; Sutartiah, Farliana (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
CV. AFW is a manufacturing industry that focuses on shelf production. One of them is a bookshelf. Currently, the company does not know the standard time for making shelves, so the production capacity cannot be determined properly. As a result, many orders accumulate and consumer complaints arise. This research discusses the determination of the standard time used to produce bookshelf products. The research was conducted using the stopwatch method (time study). Time measurements were taken using a stopwatch. Measurements were taken 81 times. The results show that the length of time required by workers in producing bookshelves is 19400,16 seconds.